2011 IEEE Third International Conference on Cloud Computing Technology and Science 2011
DOI: 10.1109/cloudcom.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Current Security Concerns and Solutions for Cloud Computing

Abstract: The development of cloud computing services is speeding up the rate in which the organizations outsource their computational services or sell their idle computational resources. Even though migrating to the cloud remains a tempting trend from a financial perspective, there are several other aspects that must be taken into account by companies before they decide to do so. One of the most important aspect refers to security: while some cloud computing security issues are inherited from the solutions adopted to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…These advance-level security challenges can be categorized into five main classes, including safety standards, network, access control, cloud infrastructure and data categories. The safety class deals with standard bodies and authorities where the lack of safety standards, compliance risks, lack of auditing [37], lack of legal aspects (SLA) and lack of trust between CSPs and cloud consumers are the focused challenging issues [46,34]. The network category issues are considered to be the most challenging since cloud computing is more prone to network-related attacks compared to the traditional computing paradigms [105].…”
Section: Other Security Issuesmentioning
confidence: 99%
“…These advance-level security challenges can be categorized into five main classes, including safety standards, network, access control, cloud infrastructure and data categories. The safety class deals with standard bodies and authorities where the lack of safety standards, compliance risks, lack of auditing [37], lack of legal aspects (SLA) and lack of trust between CSPs and cloud consumers are the focused challenging issues [46,34]. The network category issues are considered to be the most challenging since cloud computing is more prone to network-related attacks compared to the traditional computing paradigms [105].…”
Section: Other Security Issuesmentioning
confidence: 99%
“…There is no more dependence in VLAN tags to differentiate traffic flows, for instance SDN main control-data protocol is OpenFlow, which requires a flow table in data plane switches. Flow rules poorly designed or incorrectly set priorities is an additional concern to multi-tenancy in clouds Table I HOW SDN CHARACTERISTICS SOLVES OR WORSENS THE MAIN CLOUD SECURITY ISSUES categorizations, such as [25]. Paper [26] mentions VM-level attacks, abuse and malicious use of cloud computing (due to easy registration and incomplete identification of users), loss of governance (SLAs with gaps in security parameters), lock-in (when a user is unable to migrate from one service provider to another), isolation failure, data loss or leakage, management interface compromise, compliance risk, malicious insiders, insecure interfaces and APIs, and account or service hijacking.…”
Section: Security Misconfigurationmentioning
confidence: 99%
“…In [4] as well as in [25], network related issues represent 14% of stated total. In [26], network related issues are not shown explicitly under a network class, but from our analysis, 18% are related to networking, being the other issues, in general, related to access policies, computing infrastructure, and data.…”
Section: Security Misconfigurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson et al [13] have shown many security issues in different parts of cloud computing in their study. The security issues they mentioned by other researchers are in the category of network and data security, interface, virtualization, governance, compliance and legal issues which have been discussed below.…”
Section: Introductionmentioning
confidence: 99%